Validation of a 15‐item Care‐related Regret Coping Scale for Health‐care Professionals (RCS‐HCP). Issue 6 (19th January 2015) - Courvoisier, Delphine Sophie; Cullati, Stephane; Ouchi, Rieko; Schmidt, Ralph Eric; Haller, Guy; Chopard, Pierre; Agoritsas, Thomas; Perneger, Thomas V.
Abstract : Validation of a 15‐item Care‐related Regret Coping Scale for Health‐care Professionals (RCS‐HCP): Delphine Sophie COURVOISIER, et al . Department of Psychology, Harvard University, USA— Objectives: Coping with difficult care‐related situations is a common challenge for health‐care professionals. How these professionals deal with the regrets they may experience following one of the many decisions and interventions they must make every day can have an impact on their own health and quality of life, and also on their patient care practices. To identify professionals most at need for extra support, development and validation of a tool measuring coping style are needed. Methods: We performed a survey of physicians and nurses of a French‐speaking University hospital; 469 healthcare professionals responded to the survey, and 175 responded to the same survey one‐month later. Regret was assessed with the regret coping scale developed for this study, self‐report questions on the frequency of regretted situations and the intensity of regret. Construct validity was assessed using measures of health‐care professionals' quality of life (including job and life satisfaction, and self‐reported health) as well as sleep problems and depression. Results: Based on factor analysis and item response analysis, the initial 31‐item scale was shortened to 15 items, which measured three types of strategies: problem‐focused strategies (i.e., trying to find solutions, talking to colleagues) and two types of emotion‐focused strategies, A (i.e., self‐blame, rumination) and B (e.g., acceptance, emotional distance). All subscales showed high internal consistency (α>0.85). Overall, as expected, problem‐focused and emotion‐focused B strategies correlated with higher quality of life, fewer sleep problems and less depression, and emotion‐focused A strategies showed the opposite pattern. Conclusions: The regret coping scale (RCS‐HCP) is a valid and reliable measure of coping abilities of hospital‐based health‐care professionals.